Planning Daily Bread Production Using Forecasting Method and Heuristic Aggregate Method on CV. Delia Bakery - Nasha, Kayla Shawafira; Nurhasanah, Nunung; Hidayat, Syarif (JURNAL TEKNIK INDUSTRI, 2024)
CV. Delia Bakery is a home-based bakery factory located in Jatinegara, East Jakarta. It produces bread every period and currently has 30 salesmen. The amount of bread produced every period depends on the requests of each salesperson, who only asks what their target wants without any clear basis. This results in inefficient daily production levels and suboptimal profits for the company, highlighting the necessity for a well-thought-out production plan. Hence, bread production demand is predicted using the Double Moving Average forecast for 3 and 6 periods and Double Exponential Smoothing by Brown with α = 0.1. Production planning involves heuristic aggregate planning with two strategies, workforce control, and overtime control, aiming for cost-effective results. Based on the results of forecasting calculations that have been carried out using data from May and June 2023, a total of 53 periods were analyzed, revealing that the Double Exponential Smoothing by Brown method with α=0.1 achieved the lowest MAPE of 9.91%. The forecasted values for the 54th period are 9510 pcs, 55th period 9502 pcs, 56th period 9494 pcs, 57th period 9486, 58th period 9478, and 59th period 9470. The heuristic aggregate method showed that workforce control is the most cost-efficient production control strategy, costing Rp 4,800,000 over six forecasting periods.